A novel prognostic signature based on m5C‑related LncRNAs and its immunological characteristics in colon adenocarcinoma - Zihe Liu; Sheng Chang; Shouguo Chen; Rong Gu; Shaoyong Guo (Discover Oncology)
Abstract Background Colon adenocarcinoma (COAD) has high mortality rates due to frequent resistance to treatment. 5-methylcytosine (m5C) is a crucial epigenetic modification of RNA, closely associated with tumorigenesis in various cancers. This study focuses on developing an m5C-related long non-coding RNA (lncRNA) signature to predict prognosis and explore potential therapeutic targets. Methods Using data from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO), we analyzed 18 m5C regulatory genes and their associated lncRNAs in COAD samples. Prognostic lncRNAs were identified through univariate Cox regression, and a risk model was constructed through LASSO regression analyses. Kaplan–Meier survival and receiver operating characteristic analyses were employed to validate the prognostic ability of the signature. Additionally, functional enrichment and immune infiltration analyses were conducted to investigate underlying biological pathways and immune characteristics of the risk groups. Tumor mutation burden and drug sensitivity analyses were also performed. Functional validation of NR2F2-AS1 was conducted through in vitro experiments. Results We established a risk score signature comprising six lncRNAs associated with m5C regulators. Patients were classified into high- and low-risk groups based on the median risk score. This prognostic signature demonstrated significant accuracy and was independent of other clinical features. Immune cell infiltration analysis revealed correlations between the risk signature and various immune cell subtypes. Drug sensitivity analysis indicated the potential therapeutic value of our prognostic signature. Functional experiments confirmed that NR2F2-AS1 acts as a risk factor in the proliferation of colon cancer cells. Conclusions The m5C-related lncRNA signature serves as a reliable prognostic indicator for colon adenocarcinoma and provides new insights into the tumor immune microenvironment.